MASS CUSTOMIZATION: VIRTUAL-BUILD-TO-ORDER FULFILMENT SYSTEM AND ITS IMPLICATION WITH DEALER TRADING AND FORECAST ACCURACY - Mendoza Vazquez, Jair (2006)
As part of the market requirements in this era of competition and low margins, order winning criterions are the level of responsiveness and product variety; however this product variety is coined in terms of the ever more demanding needs of customers who want customized items. Emergent strategies such as Mass Customization attempts to give a solution to producers in order to satisfy these market requirements by employing inventory in process but in sectors such as the automotive industry where there is an emphasis in achieving high levels of productivity while maintaining lean, this inventory in process to reconfigure the items is just not viable. Therefore, a solution has been developed to fulfil customers from any segment of the inventory finished products, part-finished or not yet manufactured such an approach to order fulfilment is known as Virtual-Build-to-Order. The purpose of this dissertation is to perform a project within the portfolio of the Virtual-Build-to-Order (VBTO) research that is taking place in the Operations Management Division at Nottingham University Business School (NUBS) so as to study the behaviour and suitability of VBTO systems for its use as part of a Mass Customization manufacturing strategy in which the quality of the research and findings have been widely recognized by Ford, a collaborator and co-founder of the research. The study involves experimentation on a simulation model using AnyLogicTM to answer the scenario of dealer trading and forecast accuracy in open pipeline systems. The aim of this study is to examine whether the benefits of an open pipeline are dependent on the dealer performance. Dealers who are good at forecasting may be harmed by the open pipeline since dealers who are poor at it can see the pipeline too requesting the orders of good forecasters. This situation may act as a disincentive to invest in forecasting techniques however the ability of reconfiguration might soothe this risk.